2011
DOI: 10.1590/s0036-46652011000600001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of discordant immunologic and virologic responses in patients with AIDS under antiretroviral therapy in a specialized care center in Brazil

Abstract: SUMMARYSome patients under antiretroviral therapy (ART) do not reach immune recovery when the viral load becomes undetectable. This is called discordant immunologic and virologic responses. Its prevalence varies between 8% and 24%. This study describes its prevalence and the characteristics of the affected subjects in the outpatient clinic of a Brazilian specialized-care center. Of 934 patients on ART, 536 had undetectable viral loads. Prevalence was 51/536 or 9% (95% confidence interval: 6.6% to 11.4%). Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
3
8
0
3
Order By: Relevance
“…Immunologic response after 6 months of ART indicates a favourable clinical outcome in HIV-1 infected patients regardless of virologic response [ 20 ]. Several studies has reported that as many as 8–40% of patients on ART do not show a significant increase in CD4+ cell count despite viral suppression [ 18 , 21 , 22 ]. Our finding, in general, is almost consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Immunologic response after 6 months of ART indicates a favourable clinical outcome in HIV-1 infected patients regardless of virologic response [ 20 ]. Several studies has reported that as many as 8–40% of patients on ART do not show a significant increase in CD4+ cell count despite viral suppression [ 18 , 21 , 22 ]. Our finding, in general, is almost consistent with these studies.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of immunological discordant treatment response in this study population was higher than that observed in several other studies, where the proportion ranged between 9% and 28%. [ 1 , 6 8 , 10 , 24 27 ] Immunological discordant treatment response remains an unsolved challenge to physicians involved in long-term HIV care and treatment. In agreement with most other studies we found that older age was a significant risk factor for immunological discordant treatment responses.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with most other studies we found that older age was a significant risk factor for immunological discordant treatment responses. [ 1 , 6 , 7 , 9 , 10 , 15 ] The degree of immune restoration is dependent on the thymic function; as thymic function decreases with age,[ 9 , 24 , 25 ] this may explain why older people are at higher risk of incomplete immune restoration. All our patients were on a regimen including a non-nucleoside reverse transcriptase inhibitor (NNRTI).…”
Section: Discussionmentioning
confidence: 99%
“…CD4 count is being used as a marker of treatment success and is a part of patient management under our programme also. However, immune-virologically discordant responses are known to occur in 8-24% of the patients on ART [7] reducing sensitivity and specificity of the test in detecting viremic individuals. Hemoglobin and total lymphocyte count have been studied and shown to be reliable predictors of successful treatment outcome comparable to the increase in CD4 count [8].…”
Section: Introductionmentioning
confidence: 99%